Exotropia in a pediatric patient with rhabdomyolysis caused by an insect sting - Won Jae Kim; Saeyoon Kim; Myung Mi Kim (Indian Journal of Ophthalmology, 2017)
Various ocular and systemic reactions have been associated with insect sting. However, insect stings have been rarely reported to cause exotropia and diplopia. We encountered exotropia in a 6-year-old child with rhabdomyolysis of the left lower extremities caused by an insect sting. Exotropia and diplopia developed within 1 day after the sting and improved completely 1 week after the onset of symptoms. Clinicians should be aware of the potential for the development of exotropia in patients with insect stings, which requires careful follow-up.